Drosophila RecQ4 has a 3'-5' DNA helicase activity that is essential for viability. - Capp, C.; Wu, J.; Hsieh, T.S. (Journal of Biological Chemistry, 2009)
Members of the RecQ family of proteins are highly conserved DNA helicases that have important functions in the maintenance of genomic stability. Deficiencies in RecQ4 have been linked to human diseases including Rothmund-Thomson, RAPADILINO, and Baller-Gerold syndromes, all of which are characterized by developmental defects, tumor propensity, and genetic instability. However, there are conflicting results shown in the literature regarding the DNA helicase activity of RecQ4. We report here the expression of Drosophila melanogaster RecQ4 with a baculoviral vector and its purification to near homogeneity. The purified protein has a DNA-dependent ATPase activity and is a 3'-5' DNA helicase dependent on hydrolysis of ATP. The presence of 5'-adenylyl-beta,gamma-imidodiphosphate (AMPPNP), a nonhydrolyzable ATP analog, promotes stable complex formation between RecQ4 and single-stranded DNA. Drosophila RecQ4 can also anneal complementary single strands; this activity was reduced in the presence of AMPPNP, possibly because of the stable protein-DNA complex formed under such conditions. A point mutation of the highly conserved lysine residue in the helicase domain, although retaining the wild type level of annealing activity, inactivated ATPase and helicase activities and eliminated stable complex formation. These results suggest that the helicase domain alone is responsible for the DNA unwinding action of the Drosophila enzyme. We generated a null recq4 mutant that is homozygous lethal, which we used to test the genetic function of the helicase-dead mutant in flies. Complementation tests showed that the helicase-dead mutant recq4 transgenes are incapable of rescuing the null mutation, demonstrating that the helicase activity has an essential biological function.